SEXO E DENSIDADE DE CRIAÇÃO SOBRE O DESENVOLVIMENTO ÓSSEO DE FRANGOS DE CORTE COBB 500® - DOMICIANO, Carlos Henrique Leandro; OLIVEIRA, Andréia Froés Galuci; FERREIRA, Thales Silva; CASSUCI, Leticia Gabriela Talhaferro; ANDRADE, Juliana Rocha; SILVA, Taynara Mateus dos Santos (ANAIS DO ENIC, 2020)
-